The results of the complement fixation test on the cytomegalovirus antibodies in children admitted to the Gadjah Mada University, Yogyakarta - Untoro Untoro; Nelwan Nelwan; Purnomo Suryantoro; Tony Sajimin; Ismangoen Ismangoen (Paediatrica Indonesiana, 1982)
The results of the Complement Fixation Test on the cytomegalovirus (CMVV) antibodies in 138 children admitted to the Gadjah Mada University Hospital revealed seropositive conversion as high as 56.6%. The percentage of seropositive was higher in older children. This investigation suggested that seroconversion in adults might play a role in CMV infection during child bearing period.Â